A linear and non-linear evaluation of the Bell AH-1G Huey-Cobra stability and control augmentation system - De Waard, Pieter Gerrit (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbsoch, 1992.